Surrealist Signatures of Bogdan Bogdanović - Siewior, Kinga (Porównania, 2021)
The main goal of the article is to explore relations of literature and architecture in works of Bogdan Bogdanović, the Serbian architect, writer, politician and dissident. The author focuses on surrealist influences that pervade Bogdanović’s work i.e. famous memorials of WWII, sketches, political and architectural essays and autobiographical narratives. Analyzing both aesthetic and ideological aspects of surrealist signatures etched into this ouvre, the author defines them as a subversive strategy aimed against the communist discourse of Yugoslavia as well as against the modernist discourse of postwar architecture.